Quality Evaluation of Rice Crackers Fortified with Functional Plant Ingredients - Endah Puspitojati; Siwitri Munambar; Kiki Julia Ambarwati; Wildan Zacky Radithya (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
This study investigated the effects of fortification with functional plant ingredients—butterfly pea flower (Clitoria ternatea), roselle (Hibiscus sabdariffa), and ginger (Zingiber officinale)—on the physicochemical, antioxidant, textural, colour, and sensory properties of extruded rice crackers. A Completely Randomized Design consisting of four treatments (P1: control, P2:butterfly pea flower, P3:roselle, and P4:ginger addition) with triplicate experiments was applied. Results demonstrated that plant-based fortification significantly influenced proximate composition, bioactive compounds, and product quality attributes (p < 0.05). Roselle fortification produced the highest anthocyanin content and the strongest antioxidant activity, with values of 2.602 ppm and 16,059 ppm (IC50), respectively. Butterfly pea flower enhanced flavonoid content to 0.010% and achieved the highest overall sensory acceptance (score 5.00). Ginger addition significantly improved textural characteristics, particularly hardness and crispiness, with values of 63.19 N and 1.96 N, respectively, contributing to a desirable snack structure. Colour parameters were strongly affected by natural pigments derived from functional plants, enabling clean-label visual differentiation of products. Overall, butterfly pea flower (P2) was identified as the optimal formulation, providing the best balance between functional enhancement and sensory acceptance. This study introduces functional rice crackers made from broken rice with improved antioxidant capabilities, diversifying the product from rice-based raw materials. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-beingSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and Production